2011
DOI: 10.3390/molecules161210479
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents of the Methanolic Extract of Leaves of Leiothrix spiralis Ruhland and Their Antimicrobial Activity

Abstract: Chemical fractionation of the methanolic extract of leaves of Leiothrix spiralis Ruhland afforded the flavonoids luteolin-6-C-β-D-glucopyranoside (1), 7-methoxyluteolin-6-C-β-D-glucopyranoside (2), 7-methoxyluteolin-8-C-β-D-glucopyranoside (3), 4′-methoxyluteolin-6-C-β-D-glucopyranoside (4), and 6-hydroxy-7-methoxyluteolin (5), and the xanthones 8-carboxymethyl-1,5,6-trihydroxy-3-methoxyxanthone (6), 8-carboxy-methyl-1,3,5,6-tetrahydroxyxanthone (7). Methanolic extract, fractions, and isolated compounds of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Based on the criteria of Araújo [5], the evaluation of the antifungal activity of ethanol extract of Ocotea minarum , observed effective antifungal activity against the strains of Candida tropicalis in a concentration of 64 mg / mL and Candida krusei concentration of 1024 mg / ml. Strains of Candida albicans and Candida glabrata were not growth inhibited by the extract.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Based on the criteria of Araújo [5], the evaluation of the antifungal activity of ethanol extract of Ocotea minarum , observed effective antifungal activity against the strains of Candida tropicalis in a concentration of 64 mg / mL and Candida krusei concentration of 1024 mg / ml. Strains of Candida albicans and Candida glabrata were not growth inhibited by the extract.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…For the determination of minimal bactericidal concentration (MBC), a portion from each well that showed antibacterial activity was plated on Muller-Hinton agar and incubated at 37 °C for 24 h. The lowest concentration that showed no bacteria growth in the subcultures was used as the MBC. 6 Antifungal activity and minimum fungicidal concentration (MFC)…”
Section: Antimicrobial Activities Antibacterial Activity and Minimum mentioning
confidence: 99%
“…4,5 Although Eriocaulaceae are used in the manufacture of ornamental products, literature reports studies with Eriocaulaceae species that have promising antimicrobial activity. 6,7 Other studies have previously demonstrated the importance of extract and isolated substances in the Eriocaulaceae family, mainly because they present a great biological potential, such as the already identified antioxidant activities, 8,9 cytotoxic, 10,11 antiulcerogenic, 12 antibacterial and vulvovaginal candidiasis treatment. 13,14 Thus, in search of new biological compounds we described the antimicrobial activity of ethyl acetate (EtOAc) extract of capitula from Paepalanthus planifolius and its phytochemical characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementary information ( 1 H and 13 C NMR and MS spectra for the isolated compounds 1-4) is available free of charge at http://jbcs.sbq.org.br as PDF file. …”
Section: Supplementary Informationmentioning
confidence: 99%
“…For the determination of minimum bactericidal concentration (MBC), a portion from each well that showed antibacterial activity was plated on Muller-Hinton agar and incubated at 37 °C for 24 h. The lowest concentration that showed no bacteria growth in the subcultures was used as the MBC. 13 Antifungal activity and minimum fungicidal concentration (MFC)…”
Section: Fungal Growth and Extractionmentioning
confidence: 99%